Effects of lycopene on metabolism of glycolipid in type 2 diabetic rats - Yimin Yin (Biomedicine & Pharmacotherapy, 2019)
Diabetes is a series of metabolic diseases, which characteristics is hyperglycemia caused by the interruption of insulin action. Lycopene is an antioxidant which has potential anti-diabetic activity but the correlative reports are rare. This study was designed to explore the influence of lycopene on metabolism of glycolipid in type 2 diabetes. The model of type2 diabetes was induced in adult male albino Sprague Dawley rats, weighing 180-220 g, feeding high fat diet for 4 weeks, then streptozotocin (25 mg/kg) was intraperitoneally injected. 1 week after, rats in diabetic group showed increasing in fasting blood glucose, lipid in blood and liver, glycosylated hemoglobin, HOMA-IR and decreasing in plasma insulin comparing with the normal control group after modeling. Oral administration of lycopene oil solution (10 mg/kg or 20 mg/kg body weight) once a day for 10 weeks can improve the above changes and make them toward to normality. The activities of oxidative enzymes SOD and GSH-Px increased and MDA decreased in pancreatic tissue of rats after the intervention of lycopene. In addition, it can also observe that lycopene can protect body weight loss from diabetic rats. These results showed that lycopene has potential effect on anti-diabetes and it can regulate the metabolism of glycolipid in diabetic rats.